2016
DOI: 10.1080/10255842.2016.1193596
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar spine finite element model for healthy subjects: development and validation

Abstract: Finite element (FE) method is a proven powerful and efficient tool to study the biomechanics of the human lumbar spine. However, due to the large inter-subject variability of geometries and material properties in human lumbar spines, concerns existed on the accuracy and predictive power of one single deterministic FE model with one set of spinal geometry and material properties. It was confirmed that the combined predictions (median or mean value) of several distinct FE models can be used as an improved predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 51 publications
4
111
0
Order By: Relevance
“…For the stress sensitivity analysis, the intact lumbar spine model was tested in the following loading directions: compression (150 N) and Flx (10.0 N-m). According to Xu et al, the parameters were linearized to perform the stress sensitivity analysis for the model [24]. To save simulation time, the analysis did not involve annulus fibres and ligaments since Jebaseelan et al, Fagan et al and Pianigiani et al considered that the material properties of fibres and ligaments were not sensitive [25][26][27].…”
Section: Stress Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For the stress sensitivity analysis, the intact lumbar spine model was tested in the following loading directions: compression (150 N) and Flx (10.0 N-m). According to Xu et al, the parameters were linearized to perform the stress sensitivity analysis for the model [24]. To save simulation time, the analysis did not involve annulus fibres and ligaments since Jebaseelan et al, Fagan et al and Pianigiani et al considered that the material properties of fibres and ligaments were not sensitive [25][26][27].…”
Section: Stress Sensitivity Analysismentioning
confidence: 99%
“…As Xu et al suggested that ROM was a sensitivity response in the stress sensitivity analysis. Thus, ROM was chosen to test in this study [24]. Since the stress or strain results were focused on the L3-4 level, the ROM at the L3-4 level obtained by the nonlinear model, linearized basic model, high-value model and low-value model were compared.…”
Section: Stress Sensitivity Analysismentioning
confidence: 99%
“…Several factors make this retrospective analysis unique, including: (1) the large number of specimens involved (281 motion segments from 85 spines); (2) known demographics, material and geometric values;(3) biomechanical properties obtained using a consistent and precise test method (including ROM as well as the subcomponents LZ and SZ); and (4) the analysis of correlations between all of these variables. Previous similar studies, some of which also included a large number of specimens, 4,6 did not consider all of the variables analyzed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Finite element models of the lumbar spine developed from specimen-specific geometry are often validated using experimental data presented in the literature. 1,2 These data are frequently taken from a limited number of spines from both sexes with a high average age, resulting in large standard deviations, which potentially makes validation steps easier. However, based on our current findings, we propose that computational models that use specimen-specific spinal geometry may not be as accurate at predicting biomechanical outcomes as models that incorporate specimen-or at least population-specific material properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation